Sanksi bagi Perusahaan Pers yang Melakukan Tindak Sub Judice Rule dalam Perspektif Hukum Pidana Islam dan Pasal 18 Ayat (2) Undang-Undang nomor 40 tahun 1999 tentang Pers - Achmad Achmad (Sekolah Tinggi Agama Islam Taruna Surabaya, 2020)
This research is the result of library research conducted on the basis of problems that have often occurred recently, where the press has started to interfere too far in cases currently being handled by the judiciary, or rather the press has committed acts of Sub Judice Rule. This study aims to answer the questions, namely 1. What is the criminal sanction for the sub-judice rule according to Article 18 Paragraph (2) of Law Number 40 Year 1999 concerning the Press? 2. What is the criminal sanction for the sub-judice rule according to Islamic Criminal Law? The author, with the above problems, then studies and researches to solve these problems with library research using the descriptive method used to describe the concept of the sub-judice rule criminal act in Article 18 paragraph (2) of Law Number 40 of 1999 about the press. Furthermore, it is analyzed with a Deductive mindset that originates from basic principles and is combined with research using the perspective of Islamic Criminal Law. It is analyzed for specific conclusions regarding the general description of the sub-judice rule by the press according to Law No. 40 of 1999 concerning the press then draw conclusions that are specific to Islamic criminal law. The conclusion from the results of this study can be seen that the sanctions for criminal acts of the sub-judice rule contained in Article 18 paragraph (2) of Law Number 40 of 1999 concerning the press, namely, shall be punished with a maximum fine of Rp. 500,000,000.00 (Five hundred million rupiah). Sub-judice rule is a criminal act of insulting the court by means of publication, which in this case is classified as a takzir, because neither the type nor the sanctions are determined by the syarak, so that the determination of the penalty is fully left to Ulil Amri.